1996
DOI: 10.1177/1358863x9600100205
|View full text |Cite
|
Sign up to set email alerts
|

Can Lower Limb Ultrasonography Replace Arteriography?

Abstract: Although duplex ultrasonography offers a number of theoretical and practical advantages over arteriography for the assessment of lower limb arterial disease, it has not yet been widely accepted into clinical practice. This article reviews the current status of lower limb arterial duplex and concludes that arteriography should no longer be regarded as the diagnostic 'gold-standard' and that duplex ultrasonography should now be the first line investigation in patients with lower limb arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Until recently, non‐invasive imaging options included arterial duplex ultrasound and magnetic resonance imaging [3]. Although widely available, arterial duplex ultrasound can be very operator dependent and significant limitations occur with obese patients and in heavily calcified arterial segments [4, 5]. Magnetic resonance angiography has a high diagnostic accuracy, but is costly and not widely available [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, non‐invasive imaging options included arterial duplex ultrasound and magnetic resonance imaging [3]. Although widely available, arterial duplex ultrasound can be very operator dependent and significant limitations occur with obese patients and in heavily calcified arterial segments [4, 5]. Magnetic resonance angiography has a high diagnostic accuracy, but is costly and not widely available [6, 7].…”
Section: Introductionmentioning
confidence: 99%
“…The application of ultrasound in the assessment of peripheral arterial disease is an established technique that has been shown to provide comparable results to that of arteriography. 11,12 Furthermore, its utility in rapidly identifying vascular trauma within the ED setting has also been shown. [13][14][15] Radiology-performed ultrasound spares the patient the radiation exposure of CTA but is not available at all times in all EDs.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we find that DA is being investigated for this purpose. [1][2][3] Although some authors have demonstrated an acceptable correlation between arteriography and DA, [4][5][6][7][8][9][10][11][12] others have been less enthusiastic and continue to advocate preoperative or prebypass arteriography. [13][14][15][16] Some of the factors that may explain these discrepant results include:…”
Section: Duplex Arteriographymentioning
confidence: 99%